Inhibition of Transglutaminase 2 as a Potential Host-Directed Therapy Against Mycobacterium tuberculosis - Palucci, Ivana; Maulucci, Giuseppe; De Maio, Flavio; Sali, Michela; Romagnoli, Alessandra; Petrone, Linda; Fimia, Gian Maria; Sanguinetti, Maurizio; Goletti, Delia; De Spirito, Marco; Piacentini, Mauro; Delogu, Giovanni (Frontiers in Immunology, 2020)
Host-directed therapies (HDTs) are emerging as a potential valid support in the treatment of drug-resistant tuberculosis (TB). Following our recent report indicating that genetic and pharmacological inhibition of transglutaminase 2 (TG2) restricts Mycobacterium tuberculosis (Mtb) replication in macrophages, we aimed to investigate the potentials of the TG2-inhibitors cystamine and cysteamine as HDTs against TB. We showed that both cysteamine and cystamine restricted Mtb replication in infected macrophages when provided at equimolar concentrations and did not exert any antibacterial activity when administered directly on Mtb cultures. Interestingly, infection of differentiated THP-1 mRFP-GFP-LC3B cells followed by the determination of the autophagic intermediates pH distribution (AIPD) showed that cystamine inhibited the autophagic flux while restricting Mtb replication. Moreover, both cystamine and cysteamine had a similar antimicrobial activity in primary macrophages infected with a panel of Mtb clinical strains belonging to different phylogeographic lineages. Evaluation of cysteamine and cystamine activity in the human ex vivo model of granuloma-like structures (GLS) further confirmed the ability of these drugs to restrict Mtb replication and to reduce the size of GLS. The antimicrobial activity of the TG2-inhibitors synergized with a second-line anti-TB drug as amikacin in human monocyte-derived macrophages and in the GLSs model. Overall, the results of this study support the potential usefulness of the TG2-inhibitors cysteamine and cystamine as HDTs against TB.